2004
DOI: 10.1042/bj20031587
|View full text |Cite
|
Sign up to set email alerts
|

Induced oxidative stress and activated expression of manganese superoxide dismutase during hepatitis C virus replication: role of JNK, p38 MAPK and AP-1

Abstract: Activation of cellular kinases and transcription factors mediates the early phase of the cellular response to chemically or biologically induced stress. In the present study we investigated the oxidant/antioxidant balance in Huh-7 cells expressing the HCV (hepatitis C virus) subgenomic replicon, and observed a 5-fold increase in oxidative stress during HCV replication. We used MnSOD (manganese-superoxide dismutase) as an indicator of the cellular antioxidant response, and found that its activity, protein level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
87
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(96 citation statements)
references
References 53 publications
9
87
0
Order By: Relevance
“…Transfection of NS5a itself seems to be sufficient to trigger the elevation of ROS leading to the activation of several cellular transcription factors like NF-B and STAT-3 (44). Several studies demonstrated that HCV-infected liver cells in patients (45) and in vitro (46,47) are characterized by a high level of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Transfection of NS5a itself seems to be sufficient to trigger the elevation of ROS leading to the activation of several cellular transcription factors like NF-B and STAT-3 (44). Several studies demonstrated that HCV-infected liver cells in patients (45) and in vitro (46,47) are characterized by a high level of oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…As expected there is a compensatory induction of anti-oxidant defenses in cells expressing viral proteins [31] . On the other hand, expression of non-structural protein 5A (NS5A) upregulates mitochondrial ROS levels because it induces the release of calcium from ER, binds to PI3K and triggers NF-kB signaling [19,[32][33][34] . This event is followed by a translocation of NF-kB to the nucleus, where it binds to DNA and activates several gene promoters.…”
Section: Hcv and Oxidative Stressmentioning
confidence: 99%
“…ROS generation has been reported in HCV infected patients (6-8), Huh7 cells infected by an infectious clone of HCV (9), and Huh7 cells that contain HCV replicons (10,11). ROS that are located in membranes are eradicated by lipid-soluble antioxidants, such as vitamin E (12).…”
mentioning
confidence: 99%
“…This decline in lipid peroxidation allows inhibition of HCV replication without generation of cellular toxicity. (10,11), which have the potential to trigger lipid peroxidation. To monitor the production of reactive carbonyls generated by lipid peroxidation, we measured the amount of MDA produced by Huh7-K2040 cells, a line of Huh7 cells that harbor an HCV replicon (15).…”
mentioning
confidence: 99%